Odpowiedź :
a)
[tex]3(2x - y)^{2} + 2(3x + 2y)(3x - 2y) -3(x - 2y)^{2} =\\3(4x^{2}-4xy+y^{2})+2(9x^{2}-4y^{2})-3(x^{2}-4xy+4y^{2})=\\12x^{2}-12xy+3y^{2}+18x^{2}-8y^{2}-3x^{2}+12xy-12y^{2}=\\=27x^{2}-17y^{2}[/tex]
b)
[tex](2x + y )^2 - 3y(x-y) + (3x + 2y)(3x - 2y)=\\4x^{2}+4xy+y^{2}-3xy+3y^{2}+9x^{2}-4y^{2}=\\=13x^{2}+xy[/tex]
a)
[tex]3(2x-y)^2+2(3x+2y)(3x-2y)-3(x-2y)^2=[/tex]
[tex]3(4x^2-4xy+y^2)+2(9x^2-4y^2)-3(x^2-4y+4y^2)=[/tex]
[tex]12x^2-12xy+3y^2+18x^2-8y^2-3x^2+12xy-12y^2=[/tex]
[tex]27x^2-17y^2[/tex]
b)
[tex](2x+y )^2-3y(x-y)+(3x+2y)(3x-2y)=[/tex]
[tex]4x^2+4xy+y^2-3xy+3y^2+9x^2-4y^2=[/tex]
[tex]13x^2+xy[/tex]